A Nationwide Epidemiological Analysis of Finger Infections Presenting to Emergency Departments in the United States From 2012 to 2016. (March 2022) - Lemme, Nicholas J.; Li, Neill Y.; Testa, Edward J.; Kuczmarski, Alexander S.; Modest, Jacob; Katarincic, Julia A.; Gil, Joseph A.
Background: There is a paucity of literature exploring the epidemiology of finger infections presenting to emergency departments (EDs) on a national scale. The purpose of this study was to determine the national incidence of and risk factors for finger infections.Methods: Finger infections presenting to EDs between 2012 and 2016 were identified in the National Electronic Injury Surveillance System database. Finger infections were characterized by mechanism and type, with subanalyses for sex, race, and age.Results: Over this 5-year period, finger infections accounted for 80 519 visits to EDs in the United States. The annual incidence increased significantly from 4.4 per 100 000 person-years in 2012 to 6.2 in 2016. The 3 most common causes of finger infections were nail manicuring tools, knives, and doors. The most common diagnosis was finger cellulitis (46.3%). Significantly more men developed finger infections than women (relative risk of 1.4). The highest overall incidence was observed in 40- to 59-year-old men (7.8 per 100 000 person-years). Tenosynovitis resulted in the largest proportion of admissions (25%).Conclusions: We have demonstrated a rising incidence of finger infections presenting to EDs, with 40- to 59-year-old patients most at risk. The most common mechanism was the use of nail manicuring tools, such as nail clippers. Patient education may decrease finger infection incidence from these activities, and early detection of finger infections may be crucial to minimizing hospital admissions and invasive treatments.